Guidelines for strengthening community capital at Ban Talingdaeng, Kanchanaburi province - Thongoupragran, Busaba; Srisuantang, Sunti; Soopunyo, Weerachat (Kasetsart Journal of Social Sciences, 2017)
This research: 1) studied the context and community capital at Ban Talingdaeng, Tambon Nongbua, Muang district, Kanchanaburi province, and 2) explored ways to strengthen community capital in Ban Talingdaeng, Tambon Nongbua, Muang district, Kanchanaburi province. The study of context and community capital was conducted using in-depth interviews with 5 key informants obtained by the snowball technique. A transect walk and community mapping were also included. Information on ways to strengthen community capital was obtained using group discussion with purposively selected informants. A participatory process was used to encourage leaders, scholars, and members to explore and analyze the needs for enhancing the community’s existing capitalism in the field of local agricultural wisdom. Data analysis was conducted using a triangulation technique. The relationship and linkages between data groups were analyzed using contents analysis and interpretation. The results from the study showed that Ban Talingdaeng was an old community, situated along the banks of the KwaeYai River. Knowledge, cultural, and natural and environmental forms of capital were important in the village. Activities for strengthening community capital helped to support local agricultural wisdom. A network between school and community was set up using the agricultural areas of the community as a learning resource for youth. The research results revealed that the power of belief, the effective utilization and management of community capital, social network linkages, a positive attitude, team buddy focusing on participation, and the process of experimental learning and knowledge transfer were important factors for strengthening community capital.